Modern approaches to surgical and minimally invasive treatment of patients with benign prostate hyperplasia - A. A. Zimichev; D. O. Gusev; A. S. Pochivalov; P. V. Sumsky; I. V. Tarasov; D. S. Vinogradov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2020)
Adenoma of the prostate gland is one of the most common urological diseases among males. The percentage of those suffering from BPH increases in direct proportion to the age of the patients. Despite the high study of the etiology, pathogenesis and manifestations of this disease, it is not always possible to achieve the desired effect using conservative therapy. Taking into account the middle age of the majority of patients dealing  with  this  problem, the presence of a number of concomitant diseases, if there is a technical  feasibility, priority is given to the least traumatic surgical interventions. The literature review analyzes the existing approaches to surgical and minimally invasive treatment of patients with benign prostatic hyperplasia.